A remarkable new Coenosiini genus (Diptera, Muscidae) from Colombian Páramos - Fogaça, João M.; Couri, Márcia S.; Pérez, Sandra; de Carvalho, Claudio J. B. (Zootaxa, 2019)
The new genus, Sumapazomyia gen. nov., is proposed for a new species, S. inusitata sp. nov., from the National Natural Park Sumapaz, Bogota, Colombia. The unique morphology of the head and mouthparts, in combination with characters from the male and female terminalia, demonstrate that this new species represents a new and remarkable genus within the muscid tribe Coenosiini.